High-temperature-resistant low-release cyanate ester resin as well as preparation method and application thereof

By adding monofunctional cyanate and inorganic nanoparticles to the cyanate resin to form a semi-interpenetrating crosslinking network structure, the problem of insufficient temperature resistance level of cyanate resin is solved, and the dual performance improvement of high temperature resistance and low release is achieved, meeting the needs of space applications.

CN119708478APending Publication Date: 2025-03-28SHANGHAI COMPOSITES SCI & TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411839098.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing cyanate resin has insufficient temperature resistance levels and cannot meet the needs of high-temperature environments in space applications. At the same time, when improving temperature resistance, it is easy to lead to a decrease in the low release characteristics of the material.

Method used

By adding monofunctional cyanate and inorganic nanoparticles to the cyanate resin and curing in an inert atmosphere, a semi-interpenetrating crosslinking network structure is formed to improve the heat resistance and toughness of the resin while maintaining low release characteristics.

Benefits of technology

It achieves the dual performance improvement of cyanate resins with high temperature resistance and low release, meeting the needs of high temperature environments in space applications, while maintaining excellent space service characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005187527370000021
    Figure BDA0005187527370000021
  • Figure BDA0005187527370000022
    Figure BDA0005187527370000022
  • Figure BDA0005187527370000051
    Figure BDA0005187527370000051
Patent Text Reader

Abstract

The invention discloses high-temperature-resistant low-release cyanate ester resin as well as a preparation method and application thereof. The problem of insufficient temperature resistance grade of cyanate ester resin in the prior art is solved, and the application of the cyanate ester resin and a composite material thereof as a satellite or space optical telescope structure material can be met. The modified cyanate ester resin also has the following advantages: monofunctional cyanate ester is copolymerized with other cyanate ester, so that the temperature resistance grade of the resin is improved, other organic structures are not introduced, vacuum low volatilization is maintained, and inorganic nanoparticles are utilized to adjust the process property of a system, so that the space irradiation stability and atomic oxygen stability of the material are improved. The modified cyanate ester resin keeps own characteristics, and meanwhile, the manufacturability and the temperature resistance grade are improved, so that the requirements on high-temperature, low-release and size-stable resin in the fields of aerospace and the like can be met. In addition, the preparation process of the modified cyanate ester resin is simple, and mass production is easy to realize.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material preparation, and relates to a high temperature resistant low release cyanate resin and a preparation method and application thereof. Background Art

[0002] With the continuous development of aerospace technology, observation equipment such as telescopes will gradually be transported to space, opening a new round of major development in cosmic observation. The requirements for small molecule release of materials, especially condensable volatile matter, of optical equipment in space environment will be greatly increased; deep space exploration, lunar exploration and Mars exploration are gradually being put on the aerospace agenda. Spacecraft are facing new challenges such as long endurance and high power. Large energy equipment faces heat enrichment problems in a vacuum environment, which puts higher requirements on the temperature resistance of low-release materials. Some heat sinks are used at temperatures above 200°C for a long time.

[0003] Cyanate ester structural adhesive films have been widely used in spacecraft such as launch vehicles and satellites due to their advantages such as low dielectric, dimensional stability, low vacuum release, and good radiation resistance. However, the current temperature resistance grade of structural cyanate ester resins is below 180°C. Further high-temperature modification often requires the introduction of different structural thermoplastic or thermosetting resins, which reduces their inherent excellent space service properties. Therefore, it is gradually difficult to meet the needs of space applications.

[0004] At present, the methods for improving the heat resistance of cyanate resin mainly include introducing bismaleimide resin copolymerization and adding metal organic framework fillers. CN 117866432 discloses a cyanate resin with added carbon black and metal organic framework composite material, and the tensile strength retention rate of the resin at 240°C exceeds 70%, but the toughness of the resin itself is insufficient, and the room temperature tensile strength is below 50MPa, which cannot be used as a structural material. CN112111059 discloses a cyanate resin modified by blending with organosilicon oligomers, which improves the heat resistance of the cyanate resin, but the presence of oligomers will increase the vacuum volatile content of the resin. Summary of the invention

[0005] In view of the above analysis, the present invention aims to provide a cyanate ester resin having both high temperature resistance and low release and a preparation method thereof, so as to solve the problem of insufficient temperature resistance grade of cyanate ester.

[0006] The purpose of the present invention is mainly achieved through the following technical solutions:

[0007] The present invention provides a high temperature resistant, low release and high toughness cyanate resin, comprising the following components and their mass fractions:

[0008] 30-70 parts of type A cyanate;

[0009] 20-50 parts of monofunctional cyanate;

[0010] 0.3-3 parts of inorganic nanoparticles;

[0011] Catalyst 0-4 parts.

[0012] As an embodiment, the type A cyanate ester is one or more of bisphenol A cyanate ester, biphenyl cyanate ester, diphenyl sulfone cyanate ester, bisphenol E cyanate ester, and phenolic cyanate ester, and its structure is shown below:

[0013]

[0014] As an embodiment, the monofunctional cyanate ester is at least one of the monofunctional cyanate esters having the following structure:

[0015]

[0016] As an embodiment, the inorganic nanoparticles are at least one of nano-silicon dioxide, graphene oxide, and single-arm carbon nanotubes.

[0017] As an embodiment, the catalyst is at least one of zinc acetylacetonate and copper acetylacetonate.

[0018] As an implementation scheme, the curing process does not release toxic or harmful small molecule volatiles, and the curing can be completed at 120-200°C.

[0019] The present invention also provides a method for preparing the high-temperature resistant, low-release, high-toughness cyanate resin, which comprises the following steps: dispersing inorganic nanoparticles in type A cyanate in an inert atmosphere, mixing them evenly, and then melt-mixing them with monofunctional cyanate to form a homogeneous phase, adding a catalyst after cooling, and discharging the materials after mixing them evenly.

[0020] As an embodiment, the mixing temperature of the inorganic nanoparticles and the type A cyanate ester is 70-130° C., and the mixing time is 0.5-3 h.

[0021] As an embodiment, the temperature for melt mixing with the monofunctional cyanate ester is 80-150° C., and the mixing time is 0.5-3 h.

[0022] As an embodiment, the catalyst is added to the mixture at a temperature of 30-90° C. and a mixing time of 0.5-3 h.

[0023] In a third aspect, the present invention provides a use of the aforementioned cyanate ester resin, or the cyanate ester resin prepared by the aforementioned method, as a structural material for a space environment.

[0024] As an embodiment, the structural materials for space environment include structural materials for space observation equipment and spacecraft.

[0025] Compared with the prior art, the high temperature resistant and low release cyanate ester resin of the present invention has the following beneficial effects:

[0026] 1) The unique volume effect and reaction characteristics of monofunctional cyanate esters are utilized to achieve a solvation effect in the system after compounding with type A cyanate ester resin, which effectively improves the process performance of the uncured resin and satisfies different molding processes; after the resin is cured, the presence of the monofunctional cyanate ester reduces the free volume of the resin and forms a semi-interpenetrating cross-linked network structure, which improves the heat resistance of the system while ensuring the toughness of the resin;

[0027] 2) No other structural thermosetting or thermoplastic resins are introduced during the resin modification process, ensuring that the material has excellent space service characteristics, meeting the increasing demand for long-term deep space service missions, and laying a material foundation for space exploration;

[0028] 3) The resin preparation process is simple, the preparation cycle is short, the equipment requirements are low, and it is easy to engineer production. DETAILED DESCRIPTION

[0029] The present invention is described in detail below in conjunction with embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, some adjustments and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0030] Unless otherwise specified, the percentage content and percentage concentration in the present invention are all mass percentage content and mass percentage concentration. Unless otherwise specified, the raw materials can be obtained from commercial public channels.

[0031] Example 1

[0032] In a three-necked flask equipped with mechanical stirring, a thermometer and a nitrogen inlet and outlet, 100 g of bisphenol E cyanate and 1 g of nano-silica were added respectively, the temperature was raised to 145°C and stirred for 2 hours to obtain a uniform blending system, 50 g of m-maleimide cyanate was added, melt-stirred to a homogeneous phase, cooled to 40°C, 0.2 g of copper acetylacetonate was added, stirred for 1 hour and cooled to room temperature to obtain a cyanate resin.

[0033] The resin was degassed at 100°C and cured in the steps of 160°C for 1h + 180°C for 3h to prepare a cast body.

[0034] The mechanical properties, heat resistance and total mass loss in vacuum of the cyanate ester resin prepared in this example are shown in Table 1.

[0035] Example 2

[0036] In a three-necked flask equipped with mechanical stirring, a thermometer and a nitrogen inlet and outlet, 100 g of bisphenol A cyanate and 1 g of nano-silica were added respectively, the temperature was raised to 145°C and stirred for 2 hours to obtain a uniform blending system, 60 g of o-acrylonitrile was added, melt-stirred until a homogeneous phase was obtained, and after cooling to 40°C, 0.2 g of copper acetylacetonate was added, and the mixture was stirred for 1 hour and cooled to room temperature to obtain a cyanate resin.

[0037] The resin was degassed at 100°C and cured in the steps of 160°C for 1h + 180°C for 3h to prepare a cast body.

[0038] The mechanical properties, heat resistance and total mass loss in vacuum of the cyanate ester resin prepared in this example are shown in Table 1.

[0039] Example 3

[0040] In a three-necked flask equipped with mechanical stirring, a thermometer and a nitrogen inlet and outlet, 100 g of bisphenol A cyanate and 1 g of nano-silica were added respectively, the temperature was raised to 145°C and stirred for 2 hours to obtain a uniform blending system, 80 g of o-phenylpropylene cyanate was added, melt-stirred until a homogeneous phase was obtained, and after cooling to 40°C, 0.2 g of copper acetylacetonate was added, and the mixture was stirred for 1 hour and cooled to room temperature to obtain a cyanate resin.

[0041] The resin was degassed at 100°C and cured in the steps of 160°C for 1h + 180°C for 3h to prepare a cast body.

[0042] The mechanical properties, heat resistance and total mass loss in vacuum of the cyanate ester resin prepared in this example are shown in Table 1.

[0043] Example 4

[0044] In a three-necked flask equipped with mechanical stirring, a thermometer and a nitrogen inlet and outlet, 100 g of bisphenol A cyanate and 2 g of nano-silica were added respectively, the temperature was raised to 145°C and stirred for 2 hours to obtain a uniform blending system, 50 g of o-phenylpropylene cyanate was added, melt-stirred to a homogeneous phase, cooled to 40°C, 0.2 g of copper acetylacetonate was added, stirred for 1 hour and cooled to room temperature to obtain a cyanate resin.

[0045] The resin was degassed at 100°C and cured in the steps of 160°C for 1h + 180°C for 3h to prepare a cast body.

[0046] The mechanical properties, heat resistance and total mass loss in vacuum of the cyanate ester resin prepared in this example are shown in Table 1.

[0047] Example 5

[0048] In a three-necked flask equipped with mechanical stirring, a thermometer and a nitrogen inlet and outlet, 100 g of bisphenol A cyanate and 1 g of nano-silica were added respectively, the temperature was raised to 115°C and stirred for 2 hours to obtain a uniform blending system, 50 g of o-phenylpropylene cyanate was added, melt-stirred until a homogeneous phase was obtained, and after cooling to 40°C, 0.2 g of copper acetylacetonate was added, and the mixture was stirred for 1 hour and cooled to room temperature to obtain a cyanate resin.

[0049] The resin was degassed at 100°C and cured in the steps of 160°C for 1h + 180°C for 3h to prepare a cast body.

[0050] The mechanical properties, heat resistance and total mass loss in vacuum of the cyanate ester resin prepared in this example are shown in Table 1.

[0051] Comparative Example 1

[0052] In a three-necked flask equipped with mechanical stirring, a thermometer and a nitrogen inlet and outlet, 100 g of bisphenol A cyanate and 1 g of nano-silica were added respectively, the temperature was raised to 145°C and stirred for 2 hours to obtain a uniform blending system, 60 g of bisphenol E cyanate was added, melt-stirred to a homogeneous phase, cooled to 40°C, 0.2 g of copper acetylacetonate was added, stirred for 1 hour, and then cooled to room temperature to obtain a cyanate resin.

[0053] The resin was degassed at 100°C and cured in the steps of 160°C for 1h + 180°C for 3h to prepare a cast body.

[0054] The mechanical properties, heat resistance and total mass loss in vacuum of the cyanate ester resin prepared in this example are shown in Table 1.

[0055] Comparative Example 2

[0056] In a three-necked flask equipped with mechanical stirring, a thermometer and a nitrogen inlet and outlet, 200 g of bisphenol A cyanate and 1 g of nano-silica were added respectively, the temperature was raised to 145°C and stirred for 2 hours to obtain a uniform blending system, which was cooled to 40°C and 0.2 g of copper acetylacetonate was added, stirred for 1 hour and cooled to room temperature to obtain a cyanate resin.

[0057] The resin was degassed at 100°C and cured in the steps of 160°C for 1h + 180°C for 3h to prepare a cast body.

[0058] The mechanical properties, heat resistance and total mass loss in vacuum of the cyanate ester resin prepared in this example are shown in Table 1.

[0059] Comparative Example 3

[0060] In a three-necked flask equipped with mechanical stirring, a thermometer and a nitrogen inlet and outlet, 100 g of bisphenol A cyanate and 1 g of nano-silica were added respectively, the temperature was raised to 145°C and stirred for 2 hours to obtain a uniform blending system, 60 g of bismaleimide resin was added, melt-stirred until a homogeneous phase was obtained, and after cooling to 40°C, 0.2 g of copper acetylacetonate was added, and the mixture was stirred for 1 hour and cooled to room temperature to obtain cyanate resin.

[0061] The resin was degassed at 100°C and cured in the steps of 160°C for 1h + 180°C for 3h to prepare a cast body.

[0062] The mechanical properties, heat resistance and total mass loss in vacuum of the cyanate ester resin prepared in this example are shown in Table 1.

[0063] Table 1

[0064]

[0065]

[0066] In Table 1, tensile strength modulus and elongation at break: GB / T 2567; glass transition temperature: DMA method, three-point bending mode, tanδ peak temperature; total mass loss in vacuum: QJ1558A.

[0067] As can be seen from Table 1, by structural regulation, adding monofunctional cyanate ester as a reactive diluent to the traditional cyanate ester system effectively improves the temperature resistance level and toughness of the resin without losing the spatial application characteristics of the resin itself represented by low release.

[0068] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. A high temperature resistant, low release and high toughness cyanate resin, characterized in that: It includes the following components and their mass fractions: 30-70 parts of type A cyanate; 20-50 parts of monofunctional cyanate; 0.3-3 parts of inorganic nanoparticles; Catalyst 0-4 parts.

2. The cyanate ester resin according to claim 1, characterized in that The type A cyanate ester is one or more of bisphenol A cyanate ester, biphenyl cyanate ester, diphenyl sulfone cyanate ester, bisphenol E cyanate ester, and phenolic cyanate ester, and its structure is as follows:

3. The cyanate ester resin according to claim 1, characterized in that The monofunctional cyanate ester is at least one of the monofunctional cyanate esters having the following structure:

4. The cyanate ester resin according to claim 1, characterized in that The inorganic nanoparticles are at least one of nano silicon dioxide, graphene oxide, and single-arm carbon nanotubes.

5. The cyanate ester resin according to claim 1, characterized in that The catalyst is at least one of zinc acetylacetonate and copper acetylacetonate.

6. The cyanate ester resin according to any one of claims 1 to 5, characterized in that The curing process does not release toxic or harmful small volatile molecules, and curing can be completed at 120-200°C.

7. A method for preparing a cyanate ester resin according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: dispersing inorganic nanoparticles in type A cyanate in an inert atmosphere, mixing uniformly, melting and mixing with monofunctional cyanate to form a homogeneous phase, adding a catalyst after cooling, and discharging after mixing.

8. The method according to claim 7, characterized in that Include at least one of the following technical features: A. The mixing temperature of the inorganic nanoparticles and type A cyanate ester is 70-130°C and the mixing time is 0.5-3h; B. The temperature for melt mixing with monofunctional cyanate is 80-150°C and the mixing time is 0.5-3h; C. The temperature for adding the catalyst to the mixture is 30-90°C and the mixing time is 0.5-3h.

9. Use of the cyanate ester resin according to any one of claims 1 to 6, or the cyanate ester resin prepared by the method according to claim 7 or 8 as a structural material for space environment.

10. The use according to claim 9, characterized in that The structural materials for space environment include structural materials for space observation equipment and spacecraft.